Novel organosilicone adjuvants to reduce agrochemical spray volumes on row crops - Gaskin, R.E.; Elliott, G.; Steele, K.D. (New Zealand Plant Protection, 2000)
Onion and potato crops require frequent applications of highvolume agrochemical sprays The use of two novel organosilicone adjuvant blends DuWett and Bond Xtra is being developed with the aim to halve conventional spray volumes on these crops Adjuvant use rates have been optimised through extensive studies of the physical characteristics of sprays These include leaf coverage retention foliar penetration and phytotoxicity Comparisons with conventional horticultural and other organosilicone adjuvants are made to illustrate the unique properties of DuWett and Bond Xtra which can improve the retention and coverage of sprays on onions and potatoes without increasing the risk of crop phytotoxicity